Pengelolaan Sarana dan Prasarana Dalam Meningkatkan Kualitas Pembelajaran - Khaerul, Anis (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2021)
The purpose of this study was to determine the role of the Madrasah Head in managing educational facilities and infrastructure to improve the quality of learning, this study used a qualitative method. Sources of data in this study consisted of primary data and secondary data. Primary data were taken from interviews and documentation, interviews were conducted with 4 informants, namely the Head of Madrasah, Administrative Staff, Class IV Teachers and 2 Class IV students at MI MA'ARIF NU. The conclusion of this study shows that the head of the Madrasah has managerial competence, so that the Head of the MI MA'ARIF NU Madrasah plays a role in making and planning the procurement of facilities and infrastructure through meetings. In the use of facilities and infrastructure there are no written rules. Maintenance of facilities and infrastructure involves all madrasah residents in the maintenance and storage of facilities and infrastructure. Supervision of facilities and infrastructure is carried out by checking directly on the objects of infrastructure owned. The teacher's role in improving student achievement has gone well providing motivation in the learning process, using existing learning media and in accordance with the lesson plans resulting in an average academic achievement of 77 and non-academic students winning the competition so that they get an Accreditation B score.Keywords : management of infrastructure, the role of the principal, student achievement.